A Critical Observation on the Pharyngeal Teeth of Grass Carp - De, Sagnik (Indian Science Cruiser, 2013)
The pharyngeal teeth of grass carp remained intact in shape, structure, appearance and were not dislocated from the bones even after going through the entire cooking procedure which included cleaning, cutting, deep frying with oil in high temperature and boiling in water during the preparation of fish curry. Two sets of pharyngeal teeth, five in one row & four in the other were seen to be firmly fitted in the bones. The length of the saw-edged teeth were found to be 1.5cm & that of the bones were 6 -7 cm. After cleaning and taking photographs, the specimen was preserved.